Entrepreneurial orientation and the internationalization of emerging country SMEs: The mediating roles of social, industrial, and institutional network ties - Aydena, Y. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Drawing on the literature on entrepreneurial orientation (EO) and network view of internationalization, this study first investigates the impacts of EO on the degree of internationalization (DOI) of small to medium enterprises (SMEs) from an emerging country: Turkey. Second, potential network ties that SMEs establish and utilize are categorized into three different types as social, industrial, and institutional networks, and the effects of these network ties on DOI of SMEs are examined. Third, the mediating roles of various network ties in the relationship between EO and DOI are tested. Primary survey data from 401 SMEs operating in a large variety of industries from Turkey are analysed. Our findings support the hypothesized relationships and reveal the partial mediating roles of network ties between EO and DOI of SMEs.
Keywords: entrepreneurial orientation, networks, degree of internationalization, SMEs, Turkey